On a method to construct Magic rectangles of even order - De Los Reyes J.P.; Das, Ashish; Midha, Chand K.; Vellaisamy P. (Utilitas Mathematica, 2009)
Magic rectangles are well-known for their very interesting and entertaining combinatorics. In a magic rectangle, the integers 1 to mn are arranged in an array of m rows and n columns so that each row adds to the same total M and each column to the same total N. In the present paper we provide a simple and systematic method for constructing any even by even magic rectangle.